Perkembangan Usaha Koperasi Simpan Pinjam Indonesia dan Faktor yang Mempengaruhinya Periode 2013-2020 - Juri Juswadi; Pandu Sumarna (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to analyze the development of Indonesian Savings and Loans Cooperatives (SLC) during the period 2013-2020 and the trend of business performance in the future. This research is a description of development of the average credit, income, and patronage refund of Indonesia SLC during that period. It also analyze the trend of its development using trend analysis, analysis of the effect of credit on income, and analysis of the effect of income on patronage refund of Indonesia SLC. The data used in this study is survey data obtained from Savings and Loan Cooperatives Statistics 2014 to 2021, which were published by the Central Statistics Agency (BPS–Statistics Indonesia). The results of the analysis show that during the period 2013-2020 there was a fluctuating average credit, income, and patronage refund of Indonesia SLC with a relatively low trend of future developments. There is a significant effect between the average credit and the average income of Indonesian SLC and a significant effect between the average income and the average patronage refund of Indonesia SLC.